2007
DOI: 10.1371/journal.pgen.0030229
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Characterization of Cis-Acting Elements Important for Translation and Transcription in Halophilic Archaea

Abstract: The basal transcription apparatus of archaea is well characterized. However, much less is known about the mechanisms of transcription termination and translation initation. Recently, experimental determination of the 5′-ends of ten transcripts from Pyrobaculum aerophilum revealed that these are devoid of a 5′-UTR. Bioinformatic analysis indicated that many transcripts of other archaeal species might also be leaderless. The 5′-ends and 3′-ends of 40 transcripts of two haloarchaeal species, Halobacterium salinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
163
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(178 citation statements)
references
References 66 publications
10
163
1
4
Order By: Relevance
“…qRT-PCR was performed on total RNA preparations as previously described (Sherwood et al, 2009) using the iQ SYBR Green Supermix and iCycler MyiQ real-time PCR detection system (Bio-Rad) with primers specific for smrs-gfp and ribL10 (ribosomal protein). The ribL10 primers (RibL-RT_f and RibL-RT_r) were as reported elsewhere and served as a normalization control (Brenneis et al, 2007). The smrs-gfp primers were Fw, 59-ACGACTTCTTCAAGAGCG-39, and Rev, 59-CTGCCGTGATGT-ATACGT-39.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…qRT-PCR was performed on total RNA preparations as previously described (Sherwood et al, 2009) using the iQ SYBR Green Supermix and iCycler MyiQ real-time PCR detection system (Bio-Rad) with primers specific for smrs-gfp and ribL10 (ribosomal protein). The ribL10 primers (RibL-RT_f and RibL-RT_r) were as reported elsewhere and served as a normalization control (Brenneis et al, 2007). The smrs-gfp primers were Fw, 59-ACGACTTCTTCAAGAGCG-39, and Rev, 59-CTGCCGTGATGT-ATACGT-39.…”
Section: Methodsmentioning
confidence: 99%
“…Primer pairs were designed to detect the levels of smrs-gfp-specific transcript in total RNA preparations. In addition, the ribL10-specific transcript levels (encoding a ribosomal protein) were determined and served as an unregulated transcript control (Brenneis et al, 2007). The qRT-PCR analysis revealed no dramatic difference in the levels of smrs-gfp-specific transcript among the various strains (i.e.…”
Section: Reduction In Smrs-gfp Levels By Addition Of C-terminal Residmentioning
confidence: 99%
“…Long 5Ј UTRs in methanoarchaea were completely unexpected, because previous genomic and experimental analyses had predicted archaeal mRNAs to either be leaderless or possess rather short 5Ј UTRs (27). In addition, a recent systematic screen showed that the majority of haloarchaeal transcripts might be leaderless (28), and a very recent RNA-seq analysis (52) demonstrated that leaderless mRNAs are the rule in S. solfataricus P2. In contrast, the high number of long 5Ј UTRs argue for extensive posttranscriptional regulation at 5Ј UTRs in methanoarchaea (e.g., at the level of transcript stability) by regulatory proteins or RNAs, or through riboswitches.…”
mentioning
confidence: 99%
“…S2 in the supplemental material). This finding was not surprising, as leaderless transcripts are common to haloarchaea (20,21). An initial analysis was performed in wt cells to assess whether thiamine and/or its metabolic precursors could influence reporter gene expression.…”
mentioning
confidence: 83%